Inovação e empreendedorismo: uma análise das ações de estímulo e fortalecimento em universidades federais de minas gerais na década de 2010–2020 - Nivea Alves de Almeida (2021)
The objective of this study was to describe, analyze and understand the experiences of the Federal Universities of the State of Minas Gerais in the actions to stimulate and strengthen Innovation and Entrepreneurship during the period from 2010 to 2020, aiming to constitute guiding lines for the orientation of institutional development plans of Universities. Qualitative research of an exploratory and descriptive nature was adopted as a methodological strategy, through a multiple case study through the application of questionnaires and documentary research. The results allowed the construction based on the analysis categories of the study (actions of Innovation and Entrepreneurship present in the context of Universities; actions related to the fulfillment of the University's mission; actions and experiences related to the reflexes of the Technological Innovation Law and guidelines for the Plan Institutional Development (IDP)) and strategic parameters accompanied by suggestions for application in IDPs. In this way, leaders will be allowed to improve the interpretive and explanatory skills of those who study and practice Innovation and Entrepreneurship in public companies.